Investigation on the effects of Inula viscosa L. on rainbow trout gonad cells induced by lipopolysaccharide - Küçükgül, Azime; Küçükgül, Altuğ; Metin Korkmaz, Tülay (Journal of Fisheries, 2021)
Fish cells have been accepted as an alternative to in vivo assay for inflammatory effects of therapeutic experimental systems. To reveal the anti-inflammatory effects of Inula viscosa (IV) fish cell line RTG-2, derived from the gonadal tissue of rainbow trout, was infected with lipopolysaccharide (LPS). Effective concentrations for different concentrations of LPS (1, 5, 10, 20 µM) and IN (1, 5, 10, 20 µg ml–1) were determined. While the 20 µM concentration of LPS, which was effectively selected from preliminary tests, caused 27% cell loss, the effective 1 µg ml–1 concentration of IN caused 1.1% proliferation in the cells when compared to the control group. All pro-inflammatory parameters investigated in LPS-induced RTG-2 cells showed up-regulation, with the highest increase in TNF-α gene expression level (11.3 fold changes). Down-regulation was determined in the IN together with LPS administered group and IL-1β had the highest effect with 96%. IL-6 protein level decreased by LPS at a rate of 4% and IN together with LPS increased by 9%. The IN exhibited significant efficacy against inflammation caused by LPS. However, further studies are needed to determine pharmacological activity of I. viscosa in details.